Phloem : molecular cell biology, systemic communication, biotic interactions - Bel, Aart Jan Eeuwe van , 1943-; Thompson, Gary A. (Wiley-Blackwell, 2013)
Phloem: molecular cell biology, systemic communication, biotic interactions is a timely collection of research on the cellular and molecular biology of this plant vascular tissue. Recent advances in phloem research have revealed the centrality of this plant tissue to whole plant development and physiology